Implementation of an Infection Control Programme in Kano, Northern Nigeria - Abubakar, Salisu (International Journal of Infection Control, 2007)
Lack of infection control awareness among health care workers at Aminu Kano Teaching Hospital has resulted in poor waste segregation and disposal, avoidable needle stick injuries, poor suction machine/catheter care and a high rate of catheter-associated urinary tract infections (CAUTI), amongst other problems. With direction and oversight from the top management committee, a dedicated infection control nurse was appointed to implement an infection control programme within the hospital. This small infection control team has successfully promoted infection control awareness to about 90% and raised compliance to standard precautions to 86%. Waste segregation and disposal has been improved significantly and the number of sharps injuries has been reduced. As a result of improved practices, the hospital acquired infection rate decreased from 5.8% in 2003 to 2.8% by 2006. Furthermore, CAUTI and nosocomial pneumonia have dropped 33% and 6% respectively.